(untitled) (Balneo and PRM Research Journal, 2024)
Abstract: It is well known that vitamin D deficiency increases the risk of osteoporosis and that vertebral compressions fractures are a manifestation of osteoporosis. This paper presents the case of a patient with severe osteoporosis associated with vitamin D deficiency who developed over the course of two years multiple vertebral compression fractures. Method: We present the case of a 76‐year‐old caucasian female diagnosed with osteoporosis and significant vitamin D deficiency who was investigated for mechanical pain and functional deficit at the level of the spine and walking disorders. The patient was hospitalized in our Rehabilitation department twice. At the first hospitalization two years ago, the deficiency of vitamin D was found and the treatment was initiated. During the second hospitalization, biochemical and radiological investigations were per‐formed to establish the diagnosis. Numerous vertebral compression fractures were dis‐covered which were not re‐ vealed in the imaging investigations performed two years earli‐er. She underwent symptomatic and appropriate medical rehabilitation treatment. Results and discussion: The evolution was favorable after the hospitalization period, with a decrease in pain and functional deficit, as well as walking improvement. After endocrinological consultation it was decided to initiate therapy with Teripar‐ atide which can decrease the risk of future fractures and reduce the back pain. Conclusions: Ade‐ quate and prompt treatment of vitamin D deficiency and osteoporosis is very important to avoid vertebral compression fractures or other complications of this disease. Physical and rehabilitation medicine also plays an important role in management of these patients. Keywords: osteoporosis, vitamin D deficiency, vertebral compression, teriparatide